Pengaruh Kompetensi Dan Lingkungan Kerja Fisik Terhadap Motivasi kerja Pegawai (Survey Pada Puskesmas Se-Kecamatan Karawang Barat) - Sony Firmansyah; Sonny Hersona GW; Hawignyo Hawignyo (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The purpose of this study was to determine the effect of competence and physical work environment on the work motivation of puskesmas employees in West Karawang District. The research method that will be used in this research is a quantitative research method. For data analysis used in research is descriptive statistics. In addition, the research method that will be used in this study is a research method based on the formulation of an associative problem or in more detail is a causal relationship. The population in this study were all employees of the Puskesmas in West Karawang District with a total of 134 people. The samples were taken based on the results of calculations using the Slovin formula, namely as many as 100 people (rounded up) which were considered to represent the existing population. The sampling technique used in this research is simple random sampling. While the analytical tools used are path analysis, T test (partial test), F test (simultaneous), the coefficient of determination with the help of SPSS (Statistical Product and Service) software. The results showed that partially, competence had an effect on work motivation of 11.35% and the physical work environment had no significant effect on employee motivation at health centers in West Karawang District because it had an effect size of only 0.77%. Simultaneously, competence and physical work environment affect employee motivation at Community Health Centers in West Karawang District, Karawang Regency by 12.12%.